Proceedings of the 43rd International ACM SIGIR Conference on Research and Development in Information Retrieval 2020
DOI: 10.1145/3397271.3401048
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Top-Performing Precision Medicine Search Engine? Tracing Main System Features in a Systematic Way

Abstract: From 2017 to 2019 the Text REtrieval Conference (TREC) held a challenge task on precision medicine using documents from medical publications (PubMed) and clinical trials. Despite lots of performance measurements carried out in these evaluation campaigns, the scientific community is still pretty unsure about the impact individual system features and their weights have on the overall system performance. In order to overcome this explanatory gap, we first determined optimal feature configurations using the Sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…When considering the findings in TREC's precision medicine track we find a potential explanation, as it was shown that using hyponyms during term expansion has a negative effect on search rankings [12]. The search tasks we identified may be too generic, and having more specific tasks may improve the efficacy of our approach.…”
Section: Term Expansionmentioning
confidence: 90%
“…When considering the findings in TREC's precision medicine track we find a potential explanation, as it was shown that using hyponyms during term expansion has a negative effect on search rankings [12]. The search tasks we identified may be too generic, and having more specific tasks may improve the efficacy of our approach.…”
Section: Term Expansionmentioning
confidence: 90%
“…We applied information extraction pipelines to extract a variety of named entity classes. Despite the limitations we discussed, the information extracted so far can be of immediate use to enable semantic search functionalities in the guideline app (Seufferlein et al, 2019), precision medicine search engines (Faessler et al, 2020) or in clinical decision support systems (Schapranow et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The use of advanced IR techniques to improve scientific literature search has become an essential part of modern biomedical search engines [10,13,27,32]. Of particular interest to this work, the BERT contextual language model (LM) [8] and many of its extensions and variants such as ALBERT [17], SciBERT [4], or RoBERTa [20] have shown significant improvements in several natural language processing (NLP) tasks, such as question answering, named entity recognition, and passage retrieval [21,23].…”
Section: Related Workmentioning
confidence: 99%